Implementation of the Children's Digital Literacy Corner Program in Bontoala Village - Ibrahim Nur; Nasrullah Muh; Nasaruddin Hasyim (ASHA Publishing, 2026)
Implementation of the children's digital literacy corner program in Bontoala Village, Pallangga District, Gowa Regency. This study aims to describe the implementation of the children's digital literacy corner program in Bontoala Village, Pallangga District, Gowa Regency, and to find out the supporting and inhibiting factors of the children's digital literacy corner program in Bontoala Village, Pallangga District, Gowa Regency, with 7 informants. Observation, interview, and documentation methods were used in this data collection process. Data is analyzed through data condensation, data presentation, and drawing conclusions. This study confirms that in the implementation of the children's digital literacy corner program in Bontoala Village, Pallangga District, Gowa Regency, it is seen from the indicators, namely preparation, implementation, monitoring and evaluation, as well as audience and mentoring running